Peranan Guru Pendidikan Agama Buddha Dalam Meningkatkan Moralitas Peserta Didik SMK Swasta Kasih Maitreya Selatpanjang - Yanti, Yanti; Hosan Hosan; Sonika Sonika (Jurnal Maitreyawira, 2025)
This study focuses on increasing the ethical moral values ​​of Buddhist education for students. Religious education, moral ethics are important factors in realizing a complete Indonesian human being who is faithful, devoted to God, has noble character, is physically and mentally healthy, can utilize knowledge, skills for the good of many people, contributes to the harmony,progress of the nation and world. This qualitative research is a case study format, the sample is selected purposively, the participants are the leaders of the education, the teaching staff and the students of the Kasih Maitreya Private Vocational School. Collecting data by observation, interviews, documentation and triangulation. Data analysis with interactive model (miles and Huberman) through data reduction, data presentation, conclusion drawing. The validity of the data is carried out with the concept of validation in the form of triangulation, member check. The research it was found that 1. the implementation of Morality Learning at Kasih Maitreya Selatpanjang Private Vocational School has been implemented but is still not optimal, it needs to be improved again, starting from Religious, Education; moral ethics, social activities; discipline; democracy; honesty; independence; school cultures such as 5S, 3K, 3 Love, 3D, 8 Virtue; responsibility, respect for the environment. 2. The application of moral values ​​to the development of students in Private SMK Kasih Maitreya Selatpanjang has experienced a proud increase, especially in terms of increasing self-discipline, time, school rules,student participation in social and religious activities organized by the school, the Foundation.